„iDAI.world“: Die vernetzte Forschungsdatenplattform des Deutschen Archäologischen Instituts - Senst, Henriette; Riebschläger, Fabian; Watson, Juliane (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2022)
The "iDAI.world" is an integrated digital information system for researchers in the ancient sciences that can be used worldwide as a research and work platform. It consists of individual specialist systems and tools that make it possible to publish heterogeneous datasets from various disciplines like archaeology, ancient studies and other related sciences. These are linked via metadata, authority data and standards in open formats. This networked information infrastructure is operated and maintained by the German Archaeological Institute (DAI). The iDAI.world is based on tools, specialist software and systems that enable researchers to collect, visualise, publish, and archive research data as well as other research products / outputs such as excavation documentation. Therefore, a complete research infrastructure is offered that incorporates and provides documentation and publication tools and the means to integrate authority data for the ancient studies community. The iDAI.world relies exclusively on open source software and, as far as it is possible under licensing law, the data is also freely accessible and originates from cooperations with the worldwide community. As such, the iDAI.world makes an important contribution to the preservation of the cultural heritage of humankind. The module iDAI.objects (formerly ARACHNE) is operated jointly with the Research Archive for Ancient Sculpture at the Archaeological Institute of the University of Cologne.
Keywords: Research data management; Archaeology; Ancient studies